Brine-shrimp Bioassay for Assessment of Anticancer Property of Essential Oils from Spices - Bajracharya, Gan B; Tuladhar, Sarbajna M (Nepal Journal of Science and Technology, 2012)
The potential anticarcinogenicity of essential oils from spices was investigated against brine-shrimp (Artemia salina) nauplii. The essential oils were extracted by hydro-distillation. The lethal concentration at the dose levels 10, 100 and 1000 ìg/ml displayed high mortality towards actively swarming Artemia. Asafoetida (LC50 = 4.64 ×10–23 ìg/ml) and cumin oil (LC50 = 0.53 ìg/ml) were extremely toxic. Essential oils of ajowan, small cardamom, cinnamon, clove, coriander, cubeb, dill, fennel, ginger, mace, nutmeg, long pepper, rosemary, tarragon and thyme were shown high toxicity. While big cardamom oil and black pepper oil were displayed moderate toxicity. DOI: http://dx.doi.org/10.3126/njst.v12i0.6495 Nepal Journal of Science and Technology 12 (2011) 163-170